An In-depth Study on the Theories of Technology Adoption- A Review of Literature - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2020)
With time and due to diverse factors the organization needs to be dynamic. Only those organizations could survive in the competitive markets which have different strategies towards survival and tends to change as per the environment. The primary goal of the organization must be adoption of upgraded technology which they need for their business organizational growth and development.This paper aims at providing information about the theories and models related to the technology adoption.This paper deals with the secondary data and does not include any of the statistical data but only methods in a diagrammatic way. Each theory and method is designed and developed by different authors and each method/ theory has a different viewpoint and factor that contributes towards the understanding of the individual behaviour. It has been found that all the theories have been widely used and empirically have been proved by different authors.